2020
DOI: 10.3916/c63-2020-07
|View full text |Cite
|
Sign up to set email alerts
|

Influence of family and pedagogical communication on school violence

Abstract: School violence alludes to peer bullying and aggression in school. The field of communication has studied school violence by analyzing the influence of media and interpersonal relationships on aggressive behaviors. This article provides a perspective on school violence and concentrates on determining the influence of interpersonal communication with parents and teachers on adolescent aggressors and victims in school contexts. A non-experimental correlational-transverse design was used with a sample of 1,082 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
0
7
0
6
Order By: Relevance
“…Among the factors that may increase aggressiveness in children and adolescents are broken families, the absence of a parent or lack of attention, mistreatment or the use of violence-since the child learns to solve conflict through physical damage or verbal aggression-, educational methods based on permissiveness, indifference or excessive punishment, the lack of affection between spouses and the resulting insecurity of the child, the family example of "survival of the fittest" and the lack of communication. To this regard, Garcés-Prettel et al (2020) have concluded that open communication of the parents with schoolage teens contributes to the decrease and prevention of school violence. And Estévez et al (2018) found that aggressive behavior in couples is significantly related to high scores in offensive communication and family conflict, as well as to low scores in open communication with parents, general expressiveness and family cohesion.…”
Section: Means Of Communication and Technologymentioning
confidence: 99%
“…Among the factors that may increase aggressiveness in children and adolescents are broken families, the absence of a parent or lack of attention, mistreatment or the use of violence-since the child learns to solve conflict through physical damage or verbal aggression-, educational methods based on permissiveness, indifference or excessive punishment, the lack of affection between spouses and the resulting insecurity of the child, the family example of "survival of the fittest" and the lack of communication. To this regard, Garcés-Prettel et al (2020) have concluded that open communication of the parents with schoolage teens contributes to the decrease and prevention of school violence. And Estévez et al (2018) found that aggressive behavior in couples is significantly related to high scores in offensive communication and family conflict, as well as to low scores in open communication with parents, general expressiveness and family cohesion.…”
Section: Means Of Communication and Technologymentioning
confidence: 99%
“…Vinculados al contexto familiar, se encontró que los perpetradores presentan un entorno familiar negativo caracterizado por el estilo parental autoritario (padres muy exigentes y poco sensibles a las necesidades) y extremadamente permisivo (sobreprotección, baja exigencia/control) (Garaigordobil & Machimbarrena, 2017); bajo apoyo parental (Machimbarrena et al, 2019); un modelo de disciplina en la que perciben rechazo y crítica particularmente por parte del padre y poco afecto de las madres (Ávila-Toscano et al, 2021); problemas de comunicación con ambos progenitores (Carrascosa et al, 2019;Garcés-Prettel et al, 2020); y presencia de violencia en el hogar (Carrascosa et al, 2018).…”
Section: Factores Familiares Y Escolares Relacionados Con La Conducta De Bullyingunclassified
“…Asimismo, se ha demostrado que las limitaciones para informar y pedir ayuda por parte de los alumnos (Mantero-Carretero & Cervelló-Gimeno, 2019), así como la falta de claridad en las reglas y una actitud positiva hacia la transgresión de normas sociales (Romero-Abrio et al, 2019) se constituyen en predictores para la conducta de bullying. En esta línea, Garcés-Prettel et al (2020), señalan que la comunicación del profesor orientada a generar disciplina en los alumnos y hacerles ver la importancia de estudiar y aprender, contribuye a disminuir los comportamientos agresivos entre adolescentes y la victimización.…”
Section: Factores Familiares Y Escolares Relacionados Con La Conducta De Bullyingunclassified
See 1 more Smart Citation
“…Students who observe violent behaviors in educational settings, even if they do not pick sides in instances of bullying, also manifest negative consequences, such as progressive inhibition while witnessing the pain of others, little empathy and solidarity, feelings of guilt, and isolation, in the future (del Barrio et al, 2008;Simegova, 2009;Lopez et al, 2012;Estevez et al, 2019;Garces-Prettel et al, 2020;Perales et al, 2020).…”
Section: Introduction Theoretical Frameworkmentioning
confidence: 99%